Polyamines and cellular metabolism in plants: transgenic approaches reveal different responses to diamine putrescine versus higher polyamines spermidine and spermine. - Mattoo, A; Minocha, S; Minocha, R; Handa, A (2010)
Distribution of biogenic amines-the diamine putrescine (Put), triamine spermidine (Spd), and tetraamine spermine (Spm)-differs between species with Put and Spd being particularly abundant and Spm the least abundant in plant cells. These amines are important for cell viability and their intracellular levels are tightly regulated, which have made it difficult to characterize individual effects of Put, Spd and Spm on plant growth and developmental processes. The recent transgenic intervention and mutational genetics have made it possible to stably alter levels of naturally occurring polyamines and study their biological effects. We bring together an analysis of certain metabolic changes, particularly in amino acids, to infer the responsive regulation brought about by increased diamine or polyamine levels in actively growing poplar cell cultures (transformed with mouse ornithine decarboxylase gene to accumulate high Put levels) and ripening tomato pericarp (transformed with yeast S-adenosylmethionine decarboxylase gene to accumulate high Spd and Spm levels at the cost of Put). Our analysis indicates that increased Put has little effect on increasing the levels of Spd and Spm, while Spd and Spm levels are inter-dependent. Further, Put levels were positively associated with Ala (alpha and beta), Ile and GABA and negatively correlated with Gln and Glu in both actively growing poplar cell cultures and non-dividing tomato pericarp tissue. Most amino acids showed positive correlations with Spd and Spm levels in actively growing cells. Collectively these results suggest that Put is a negative regulator while Spd-Spm are positive regulators of cellular amino acid metabolism.